The Mini United Nations Adult School in Southwest Kansas - Susan Lukwago (Educational Considerations, 2007)
Traveling down Kansas Avenue towards downtown Liberal at about 5:30 p.m. on Monday through Thursday, one might wonder what happens in the little building at the corner 10th and Kansas.
Keywords: Seward County Community College (SCCC); Southwest Kansas; Adult Learning; multicultural; program